Understanding global administrative law - Della Cananea, Giacinto (Leiden, Netherlands : Brill ; Boston : Nijhoff, 2025)
Global administrative law is recent, but increasingly important, as it has an impact on a wide range of areas. This book analyzes it in three ways. First, it examines the main elements of global administrative law, including its social basis and a variety of global standards. Second, it shows that the inter-relationship between various levels of government (domestic and global) is important and occurs in more than one way, including networks of public authorities and mixed administrative procedures. Third, it argues that these inter-relationships are problematic, because there is sometime collision between legal systems and even overlapping jurisdictions.
Keywords: Derecho administrativo